2021
DOI: 10.3390/en14061592
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust Noise Reduction by Application of Expanded Collecting System in Pneumatic Tools and Machines

Abstract: In this paper, we demonstrate how to reduce the noise level of expanded air from pneumatic tools. Instead of a muffler, we propose the expanded collecting system, where the air expands through the pneumatic tube and expansion collector. We have elaborated a mathematical model which illustrates the dynamics of the air flow, as well as the acoustic pressure at the end of the tube. The computational results were compared with experimental data to check the air dynamics and sound pressure. Moreover, the study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Grybos et al demonstrated how to reduce the level of noise from the expanded air from pneumatic tools [4]. Instead of a muffler, an expanded collecting system was proposed, where the air expands through the pneumatic tube and expansion collector.…”
Section: Published Papersmentioning
confidence: 99%
“…Grybos et al demonstrated how to reduce the level of noise from the expanded air from pneumatic tools [4]. Instead of a muffler, an expanded collecting system was proposed, where the air expands through the pneumatic tube and expansion collector.…”
Section: Published Papersmentioning
confidence: 99%
“…As mentioned above, the main drawback of compressed air systems is their low energy efficiency, with only 5-10% of the electrical energy input to the compressor effectively being utilized in pneumatic actuators or motors [1,9]. Other disadvantages of compressed air systems include low precision in motion control [10], noise [11,12], and significant air leaks [1]. As a result, the Compressed Air and Gas Institute (CAGI), the European Association of Manufacturers of Compressors, Vacuum Pumps, Pneumatic Tools and Air and Condensate Treatment Equipment (PNEUROP), and entrepreneurs are actively looking for solutions to address this energy loss issue [13,14].…”
Section: Introductionmentioning
confidence: 99%